Fathers, food practices and the circuits of intimacy in families in Northern England. Issue 8 (3rd August 2017) - Meah, Angela
Abstract: Informed by a 'theories of practice' approach and moving beyond accounts that emphasise domestic foodwork as a wholly feminised task, this article draws upon a series of ethnographic studies undertaken in Northern England to examine men's frequently overlooked contributions to feeding the family. Deploying the idea of 'circuits of intimacy', it specifically highlights how shopping, cooking and eating form part of the daily emotional practices through which contemporary fathering is negotiated, contested and resisted. In doing so, it contributes to debates concerning fathering and the spaces in which it is undertaken – areas of enquiry that have, until recently, remained relatively hidden in geographical research – as well as addressing the issue of feeding and family intimacy which has been underexplored within studies of fathering.